Cultural Resistance through the Manuscrit Moderne: Tériade’s editions of Rouault’s Divertissement and Bonnard’s Correspondances - Swan, Rodney (RELIEF - REVUE ÉLECTRONIQUE DE LITTÉRATURE FRANÇAISE, 2017)
Inspired by the politico-cultural significance of the French medieval manuscript, the Greek born publisher Tériade created its modernised counterpart, his manuscrit moderne, pushing the artists’ book to new innovative heights in France during the Second World War. Tériade commissioned Georges Rouault’s Divertissement (1943) and Pierre Bonnard’s Correspondances (1944) during the darkest days of the Occupation, and in a historic reversal of the process, these artists created their images, embedded with codes and symbols of resistance, before they authored the text. The wartime manuscrit moderne with its handwritten text set the preconditions for this new genre to flourish after the Liberation.